Ergo-Iconic Value and Local Products as Media of Generation Z Consumption Identity - Andriyansah Andriyansah (AIBPM Publisher, 2024)
This article develops a conceptual framework for understanding ergo-iconic value in local products as a mechanism for transmitting Generation Z consumption identity. Using an integrative literature review and theory synthesis, the article connects product value theory, symbolic consumption, consumption identity, digital consumer experience, and the emerging body of literature on ergo-iconic value. The central argument is that local products become meaningful to Generation Z when functional usefulness, symbolic recognition, and digital communicability are mutually connected. Ergo value provides functional legitimacy by enabling local products to be accepted as useful, reliable, accessible, and relevant to everyday consumption. Iconic value provides identity legitimacy by enabling local products to be recognized as distinctive, meaningful, authentic, and identity-bearing. Digital articulation allows these values to circulate through social media, marketplaces, electronic word of mouth, user-generated content, and online communities. The proposed framework consists of four interrelated components: local product base, ergo value, iconic value, and digital articulation. These components generate three processes of consumption identity transmission: functional internalization, symbolic recognition, and digital articulation. The article contributes to product value and consumption identity literature by repositioning local products not merely as commodities or cultural artifacts, but as value-bearing media through which function, identity, and digital experience are integrated. The framework also offers a basis for future empirical research on how younger consumers interpret, display, and negotiate local product meanings in digital consumption environments.